COST ACCOUNTING IN THE SIXTEENTH CENTURY. - Edler, Florence (The Accounting Review, 1937)
Abstract It is a generally accepted belief that cost accounting originated in the nineteenth century and received its major impulse from the development of the factory system and the extensive use of machinery in industrial production. This common opinion is only partly true. A systematic technique of cost accounting was developed during the nineteenth century and has been greatly extended in recent decades, but some elements of cost accounting are much older. Existing medieval business records show that industrial accounts were used as early as the beginning of the fourteenth century. This fact has been brought to light by recent research in old Italian account books, such as those of the Del Bene Company, Florentine importers and finishers of foreign woolen cloths in the first part of the fourteenth century. For the sixteenth century, examples of industrial bookkeeping are also found in the records of German mining enterprises. All these examples demonstrate beyond a doubt that rudimentary forms of cost finding were commonly adopted in those industries such as mining and textiles, which came under capitalistic control centuries before the Industrial Revolution.